NUMERICAL SIMULATION OF ULTRA-HIGH-PERFORMANCE CONCRETE’S COMPRESSIVE AND TENSILE BEHAVIOUR IN BEAMS - Jabbar, Adil; Danha, Lubna; Abdulmajeed, Qais (Journal of Applied Engineering Science, 2023)
Ultra-high-performance concrete (UHPC) differs in its structural behavior from conventional concrete due to its high compressive and tensile strength, stiffness, toughness, and durability. Therefore, UHPC needs an appropriate constitutive model to simulate its mechanical properties in finite element analysis. In this study, numerical models were developed to trace the structural behavior of UHPC beams upon loading since beam behavior depends on the constituents’ response to compression and tension. New numerical models were formulated to display the stress-strain relationships of UHPC in compression and tension by adopting a new methodology that depended on actual results. The compressive stress-strain relationship included two portions; the ascending one for elastic and strain hardening up to compressive strength and a descending curve for the strain-softening until a 0.0062 strain. A linear elastic tensile stress-strain relation was applied until tensile strength. A tri-linear relationship was applied for stiffness degradation and crack propagation upon debonding fibers from the matrix until fracture. These numerical models were used in Abaqus software to simulate the UHPC beam behavior. The developed models were verified and proved for beams’ behavior in flexure and shear. The results indicated that the models could predict UHPC beams’ response throughout the entire loading until failure.